The Difficulty in the Implementation of Accounting Standard for Non Publicly Accountable Entities - Sulistyawati, Ardiani Ika; Lestari , Erika Puji; Nugroho, Arief Himmawan Dwi; Gusmao, Cristino; Santoso, Aprih; Rosyati (Jurusan Akuntansi Politeknik Negeri Malang, 2024)
Abstract: The Difficulty in the Implementation of Accounting Standard for Non-Publicly Accountable Entities Purpose: The research seeks to investigate the application of SAK ETAP in financial report of a non-publicly accountable entity. Method: Observational data collection techniques, documentation, interviews, and literature reviews with qualitative descriptive research methodologies were used to obtain and analyze data and to formulate findings.Results: The study results on Lottery Billiard and Cafe reveal that they still use single-entry or cash-based bookkeeping for their financial reports, leading to inaccuracies in the recording process. Additionally, the capital account is not reported, even though revenue should be recorded in the revenue account. The financial records do not adhere to the SAK ETAP standards.Novelty: The application of this research is in a specific context that focuses on SAK ETAP and the integration of several strategic analysis frameworks to identify the most appropriate approach Lotter Billiard and Cafe.Contribution: This research not only answers current challenges for Lotter Billiard and Cafe, but also the broader discourse on SAK ETAP implementation. Abstrak: Kesulitan Penerapan Standar Akuntansi Keuangan bagi Entitas Non-Akuntansi Publik Tujuan: Penelitian ini menggali penerapan SAK ETAP dalam laporan keuangan pada sebuah entitas tanpa akuntabilitas publik.Metode: Koleksi data dilakukan melalui observasi, dokumentasi, wawancara, dan studi kepustakaan, dilanjutkan analisis data kualitatif deskriptif untuk menghasilkan temuan.Hasil: Hasil penelitian tentang Lottery Billiard and Cafe menunjukkan bahwa pencatatan pembukuan single entry atau cash basis masih digunakan dalam laporan keuangan, sehingga terdapat beberapa ketidakakuratan dalam pencatatan keuangan selama penerapannya. Lotter Billiard and Cafe tidak melaporkan akun modalnya, meskipun pengakuan pendapatan seharusnya didokumentasikan dalam akun pendapatan. Pencatatan keuangan yang digunakan tidak mengikuti pedoman SAK ETAPKebaruan: Penerapan penelitian ini berada pada konteks spesifik yang berfokus pada SAK ETAP dan integrasi beberapa kerangka analisis strategis untuk mengidentifikasi pendekatan yang paling tepat yaitu Lotter Billiard and Cafe.Kontribusi: Penelitian ini tidak hanya menjawab tantangan pada Lotter Billiard and Cafe, namun juga wacana yang lebih luas mengenai implementasi SAK ETAP.